Luminescence dating of heated quartz extracted from burnt clay and pottery excavated from the Lingjiatan archaeological site, China - Wang, Chun-Xin; Zhang, Xiaolei; Zhang, Yunyi; Wu, Youjin; Huang, Chang; Fan, Anchuan (Frontiers in Earth Science, 2022)
This study utilizes OSL-SAR, TL-SAR and TL-MAAD methods to date heated quartz extracted from burnt clay and pottery samples from the Lingjiatan archaeological site, China. The OSL components of the heated quartz were determined by deconvoluting the CW-OSL curve, and the Fast Ratio value was used to distinguish whether the initial OSL signal was dominated by the fast component. The results show two types of quartz OSL characteristics in the initial signals: Type I is dominated by the fast component (Fast Ratio values >10), while Type II is dominated by the medium and slow components (Fast Ratio values <10). Type I samples show bright OSL signals, and a preheat plateau appears from a relatively low temperature. The recuperation is negligible, and reliable equivalent doses can be obtained using the conventional OSL-SAR measurement conditions. In contrast, the OSL signal of Type II samples is relatively dim, and the preheat plateau appears from a much higher temperature than in Type I samples. The recuperation of Type II samples increases significantly at higher preheat temperatures. Significant De underestimation of Type II samples was observed at lower preheat temperatures. It is noted that the thermal transfer effect can be attenuated by increasing the OSL stimulation temperature. Therefore, a modified OSL-SAR measurement condition, with higher preheat, cut-heat and stimulation temperatures, was used to date Type II samples. The OSL-SAR ages of most of these two types of samples agree well with the independent 14C ages, demonstrating that OSL-SAR can be used to date heated archaeological materials at high firing temperatures (~900 °C). The Lingjiatan archaeological site was determined to be approximately 5.4-5.8 ka BP2022.